Physical and Chemical Methods Used for Determination of Structures of Some Imines Derived from Different Carbonyl Compounds - Adel S.P.Azzouz; D. B.T.Bakzo (College of Education for Pure Sciences, 2018)
The project is concerned with the preparation of fifteen imines derived from 2-acetyl pyridine ,3 or 4 -hydroxy benzaldehyde and m-anisaldehyde with aromatic primary amines by standard method . These imines include namely ,hydroxylamine hydrochloride,o,m,p-amino phenols ,4-amino naphthol ,bromo or chloro aniline and p-anisidine . The main aims of the study is the determination of structures of these imines by the available physical method ,namely ,the melting points ,boiling points , U.V and IR spectra . Some chemical tests for functional groups are also included .This seems important from chemistry point of view as in the elucidation of tautomerism reactions happen in some oximes and phenolic oximes . Finally ,the influence of inter molecular hydrogen bonding on association (polymerization) of imines was also discussed